Cannabis: between illegal drug and booming business. Are traditional stereotypes changing in the Spanish press? - Santos Diez, María Teresa (2022)
The objective of this article is to analyze the treatment of cannabis from the perspective of the Spanish newspapers in order to show the image they offer. Using a content analysis methodology, the genres, the sources used, the dominant thematic areas are identified and the treatment given by the Spanish digital newspapers El País, El Mundo, ABC and La Razón, from January 1 to December 31, 2019, is compared. The findings show a predominance of informative texts, signed by the editors or the newspaper itself and a use of official sources. Regarding their subject matter, the newspapers continue to relate cannabis to actions typified as crimes (arrests, dismantling and seizures). Likewise, they incorporate new contents related to this substance, such as the business of production, distribution, biotechnology, cosmetics and leisure companies, which appear as an emerging sector. It also highlights the absence of information on programs, services and campaigns carried out by Institutions and other organizations to face problems of dependency or addiction, among others. These results suggest that legislative changes show the need to carry out a process of normalization of the status of cannabis, which tends to relate it to health, personal care, leisure and even luxury. Thus, Spanish newspapers are beginning to move away from the perception of cannabis as an illegal drug that has been maintained for decades, to show a somewhat more permissive image of cannabis, ignoring other aspects.